The Concept Of People’s Economy Based On Pancasila As Legistimation Of Economic Ideology In Indonesia - Ahmad Baiza (SMARTINDO, 2023)
The concept of populist economy based on Pancasila is a concept from the thinking in planning and implementing economic development at the national level. Where the frame of mind is based on the elaboration of the values contained in the Pancasila paradigm. The establishment of a Pancasila-based populist economy as the legitimacy of economic ideology in Indonesia is crucial by looking at the phenomenon of global capitalism in overcoming a decline in economic stability. The people's economy itself has deviated far from the existence of a liberalist economy and capitalism which will eventually have the impact of economic inequality for the community. The purpose of this study is to see the existence of the Pancasila-based populist economic concept, whether it is still feasible and whether it has been properly implemented as a legitimacy for economic ideology in Indonesia. The method of this study uses a systematic literature review method in which this method must be consistent with the latest suggestions where the management literature review must be strengthened. In carrying out the selection of literature reviews for data collection and analysis, there must be the latest conceptual development and mapping. This study found that Indonesia has not been able to perfectly apply the concept of populist economy based on Pancasila. Even though Indonesia supports the concept of a Pancasila-based populist economy, its implementation in the field has not been fully fulfilled. Where the nation's capital ownership or foreign investors still dominate the economic aspects in Indonesia.